Novel plant-based compounds could be useful in protecting shrimp species against AHPND Vibrio parahaemolyticus - Kumar, Vikash; Bossier, Peter (Journal of the Inland Fisheries Society of India, 2020)
The acute hepatopancreatic necrosis disease (AHPND), originally known as early mortality syndrome (EMS) is a newly emerging shrimp disease causing havoc in the shrimp industry (De Schryver et al., 2014). The disease is caused by specific virulent stains of Gram-negative marine bacterium, Vibrio parahaemolyticusubiquitous in estuarine and coastal waters (FAO, 2018). Since the AHPND outbreak first appeared in China in 2009, it has spread to Vietnam (2010), Malaysia (2011), Thailand (2012), Mexico (2013), Philippines (2015) and South America (2016) (Lai et al., 2015; Lee et al., 2015). The shrimp production in AHPND affected regions has dropped to ~60%, and the disease has caused global loss of $1 billion per year to the shrimp farming industry (Kumar et al., 2019, 2018). The V. parahaemolyticus becomes virulent VPAHPND by acquiring a 63-70 kbplasmid (pVA1) encoding the binary toxin PirAVp/ PirBVp, which consist of two subunits PirA and PirB, and is homologous to the Photorhabdus luminescensinsect-related (Pir) toxins PirA/PirB(Sirikharin et al.,2015). The binary toxin PirAVP and PirBVP damages theshrimp tissue, primarily the hepatopancreas (Hp) R(resorptive) cells, B (blister) cells, F (fibrillar) cells and E(embryonic cells), resulting in shrinkage of Hp tubularepithelial cells and sloughing of Hp tubular lumen. Theearly life stages of shrimp are often found to be moresusceptible to the pathogenic AHPND V. parahaemolyticus infection the infection develops quickly,starting approximately after 8 days of post larvaestocking and severe mortalities occurs during the first20-30 days of culture (Choi et al., 2017).